A METHOD FOR IMPROVING THE PERFORMANCE EVALUATION OF NARROWBAND WIRELESS MESH NETWORKS - MIKHNENKO, YAROSLAV; KONONOVA, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article deals with the problem of evaluating the performance of narrowband wireless mesh networks, which are the basis for creating highly reliable communication systems in conditions of limited radio frequency spectrum resources. Particular attention is paid to the study of the peculiarities of network operation in the relay node modes. It is established that the efficiency of narrowband wireless mesh networks significantly depends on the settings of data transmission parameters: message size, modulation rate, use of short acknowledgments and direct error correction mechanisms.A systematic approach to evaluating the key parameters of network performance is proposed: data transmission rate, packet transmission time, probability of successful message delivery, and calculation relations for determining the packet transmission time and payload bitrate with regard to service information are given.Particular attention is paid to the mechanism of confirming the delivery of packets through a short message of confirmation of receipt of a data packet, in particular, the impact of retransmissions on the overall network throughput. It is shown that the use of direct error correction schemes helps to reduce the impact of radio channel interference and improve communication reliability, but increases the overall data transmission time. The results of the study allow us to formulate recommendations for optimizing network parameters and demonstrate a clear relationship between transmission characteristics and network performance to ensure guaranteed message delivery. The obtained measurements of key parameters provide the basis for an objective and accelerated analysis of the performance of narrowband wireless mesh networks in applied conditions, and also confirm the feasibility of using the proposed approach to improve the accuracy and informativeness of the assessment.
Keywords: narrowband wireless mesh networks; data packets; performance evaluation; error correction; performance